The multidimensional role of the English for specific purposes practitioner in today’s changing societies: voices from around the globe - Kakoulli-Constantinou, Elis (My University, 2023)
English is one of the most widely taught languages not only in Europe but across the globe, being the language of international communication, science and technology. It is nowadays an integral part of Higher Education curricula in many countries, as English for Specific Purposes (ESP) is considered essential for the acquisition and development of students’ employability skills. Simultaneously, the economic, political, social and technological developments occurring during the last decades have made the role of the ESP practitioner more complex and important at the same time. Nevertheless, issues related to the role, needs and duties of the ESP practitioners have not been adequately explored by researchers in the field. This paper focuses on the multifaceted role of the ESP practitioner stemming from the specialised needs of learners and the multiple duties they are expected to perform. More specifically, the paper reports on the results of a Technical Action Research study conducted with 24 English language educators across the globe, who wished to receive education on issues pertaining to ESP teaching methodology or update their knowledge on the latest development in ESP teaching practices. Data were collected through an online questionnaire, field notes, reflective journals, comments on an online platform and focus groups/interviews. The results shed light on the profiles of ESP practitioners, their duties and teaching contexts, the challenges they face, and their need to receive education on ESP issues.
Keywords: ESP practitioner; ESP training; Language educators; Teaching context